Quantification of marrow hematogones following autologous stem cell transplant in adult patients with plasma cell myeloma or diffuse large B-cell lymphoma and correlation with outcome. Issue 4 (3rd April 2018) - Santiago, Victor; Lazaryan, Aleksandr; McClune, Brian; McKenna, Robert W.; Courville, Elizabeth L.
Abstract: In this retrospective study, we quantified the hematogone (normal B-lineage precursor) population by flow cytometric immunophenotyping in post-transplant bone marrow biopsy specimens from adult patients who received an autologous stem cell transplant for either plasma cell myeloma (n = 57) or diffuse large B-cell lymphoma ( n = 73). The majority of patients (80%) had <5% marrow hematogones post-transplant. Extreme (>10%) hematogone percentages were quite rare, seen in only four patients, and were not associated with disease progression. There was a positive association between the post-transplant day and hematogone percentage within the first year after transplant, and a negative association thereafter. Plasma cell myeloma patients with ≥5% hematogones in any post-transplant flow cytometry study had a worse overall survival as did plasma cell myeloma patients with increased hematogones (as defined by percentile) at 100 days post-transplant. These findings require further study, ideally in a prospective study design.